Caravana pescador amigo: sensibilização e capacitação para o desenvolvimento da pesca responsável - Bertozzi, Carolina Pacheco [UNESP]; Santos, Thais Cruz Alves; Monteiro, Rafael Araujo Arosa; Motta, Nathália Sousa; Silva, Lygia Moraes Cardoso; Perri, Ilka Izadora da Silva; Magrini, Emily; Aparecido, Katia Cristina; Zanoni, Gustavo Andrade (Universidade Estadual Paulista (Unesp), 2015)
Global main marine fish stocks are pressured by overfishing or categorized as endangered species due to intense fisheries activities. Brazil follows national and international laws related to biodiversity conservation, among these, the Code of Conduct for Responsible Fisheries, FAO, which promotes and encourage sustainable fisheries to preserve the marine environment. This work was developed to promote information, qualify and to provide knowledge to artisanal fishermen about responsible fisheries practices. It was developed the “Caravana Pescador Amigo” and the “Cartilha Pescador Amigo”. The Caravana was realized in three steps/courses: Step 1. Workshop of participatory diagnosis “Biomapa da Pesca”; Step 2. Sustainable entrepreneurship and Step 3. Responsible Fisheries Practices. The “Cartilha Pescador Amigo” was developed as a didactic material to the courses of the Caravana. A total of 601 fishermen from twelve fisher communities of eight cities of São Paulo´s littoral, participated directly of the activities from july 2014 to june 2015.

A intensa exploração pesqueira tem levado diversas espécies à situação de sobrepesca ou de ameaça de extinção. O Brasil é signatário de diversos tratados nacionais e internacionais relacionados à conservação da biodiversidade, entre eles o Código de Conduta para a Pesca Responsável, FAO, o qual norteia e incentivam as atividades de pescas sustentáveis e em harmonia com o meio ambiente. Com o objetivo de levar informação, conhecimento e capacitar pescadores artesanais sobre práticas de pesca responsáveis foi desenvolvida a Caravana Pescador Amigo e a Cartilha Pescador Amigo. A Caravana foi desenvolvida em três etapas: Etapa 1. Oficina Diagnóstico Participativo Biomapa da Pesca; Etapa 2. Curso Empreendedorismo Sustentável e Etapa 3. Práticas de Pesca Responsável. A Cartilha Pescador Amigo foi elaborada como um material de apoio aos cursos. Um total de 601 pescadores de doze localidades pesqueiras de oito municípios do litoral de São Paulo participaram diretamente das atividades da Caravana Pescador Amigo, no período de julho de 2014 à junho de 2015.
Keywords: Responsible fishery; Conservation; Qualify; Pesca responsável; Conservação; Capacitação